2015
DOI: 10.1128/genomea.00388-15
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequence of Rhodovulum sulfidophilum DSM 2351, an Extracellular Nucleic Acid-Producing Bacterium

Abstract: Rhodovulum sulfidophilum DSM 2351 is the nonsulfur photosynthetic bacterium that efficiently releases nucleic acids into the extracellular milieu, which leads to flocculation. In this study, we determined the complete genome sequence of R. sulfidophilum DSM 2351, which will provide new insights into the mechanism of its unique nucleic acid release.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 9 publications
0
15
0
Order By: Relevance
“…The genome size, G+C content, and the number of CDS, rRNA operon, tRNA genes, and plasmids in these strains are shown in Table 2 in comparison with those of Rhv. sulfidophilum DSM 2351 [63]. The chromosome size of Rhodovulum sp.…”
Section: Genomic Analysis Of Rhodovulum Strainsmentioning
confidence: 99%
See 1 more Smart Citation
“…The genome size, G+C content, and the number of CDS, rRNA operon, tRNA genes, and plasmids in these strains are shown in Table 2 in comparison with those of Rhv. sulfidophilum DSM 2351 [63]. The chromosome size of Rhodovulum sp.…”
Section: Genomic Analysis Of Rhodovulum Strainsmentioning
confidence: 99%
“…A phylogenomic analysis of 25 strains of Rhodovulum species on which whole-genome information is available (Table S3) [63,[69][70][71] was performed on the basis of 92 protein-coding gene sequences. The reconstructed phylogenomic tree revealed that Rhodovulum sp.…”
Section: Genomic Analysis Of Rhodovulum Strainsmentioning
confidence: 99%
“…The physiological relationship between the production profiles and the cultivation conditions used in this study might be explained by further quantitative analyses, as it appeared that strain DSM1374 T cultivated with richmedium under dark-condition produced C 20 -HSLs at a relatively high level. The recent revelation of the genome sequences in both strains [9,10] will likely facilitate further elucidation of regulation and function of genes involved in AHL production.…”
Section: Discussionmentioning
confidence: 99%
“…R. sulfidophilum can grow not only under anaerobic-light conditions but also under aerobic-dark conditions with an appropriate carbon source, forming small flocs when cultivated in nutritionally rich medium albeit constructing huge flocs in nutritionally poor medium [7]. Strain DSM1374 T is the type strain of R. sulfidophilum and strain DSM2351 is closely related with 99.6% similarity in 16S rRNA sequence [8][9][10], although it has been indicated that DSM2351 shows a higher flocculation rate than that of DSM1374 T during cultivation [7]. In our previous study, it was shown that alpha-cyclodextrin (α-CD), which traps the extracellular AHLs and inhibits quorum sensing [11], does not inhibit the cell growth and floc formation of R. sulfidophilum DSM2351 whereas the matured floc structure was disrupted in the presence of α-CD [7].…”
mentioning
confidence: 99%
“…For such medical applications, extensive genetical and physiological elucidation of this bacterium is important, especially from the viewpoint of the rigorous production demands of medicines. Accordingly, the complete genome sequences of several strains of this bacterium have been determined by us and others (Guzman et al, 2017;Masuda et al, 2013;Nagao et al, 2015a).…”
mentioning
confidence: 99%